Malaysian teachers’ perceptions regarding the impact of the choice of topic on ESL learners’ motivation in writing - Mohammad Affiq Kamarul Azlan; Khairul Hisyam Baharuddin; Wan Yusoff Wan Shaharuddin (2014)
A number of researches have investigated whether or not the choice of topic for writing will impact ESL learners’ motivation to write. Yet, most of these studies were conducted in the environment where English is used as first language. Though several studies were conducted in a second language environment, the socio-cultural backgrounds of the environment do not reflect the situation in Malaysian education system. This study thus investigates Malaysian teachers’ points of view regarding the impact of the choice of topic on ESL learners’ motivations in writing. Specifically, this research aims to identify whether the suggested motivating factors to be considered in selecting topics for writing by previous researches are applicable in Malaysian context as well as to identify other factors Malaysian teachers believe should be considered when selecting topics for writing in order to increase learners’ motivation to write. A number of school English teachers were interviewed regarding the relation between the choice of topics and learners’ motivation in writing. A group of pupils were interviewed to find what factors affect their motivation to write. The findings suggest that learners’ socio-cultural background, prior knowledge and audience are important determiners of their motivation in writing, while learners’ experiences and teachers’ rewards are other factors that matter in the Malaysian context.